2021
DOI: 10.1007/s00170-021-06733-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tool point angle and interlayer gap width on interface borehole quality in drilling CFRP/titanium stacks

Abstract: Although substantial research work has been conducted in order to understand and improve the drilling of multi-material aerospace stacks, some key aspects related to process and tool parameters and their impact on the interface quality still need to be addressed. This paper reports on the research conducted to investigate the impact of tool point angle and interlayer gap width on borehole quality, focussing on the interface region. A number of drilling tests were carried out using tools with different point an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Геометрія різального інструмента, інструментальний матеріал та покриття є важливими факторами, які впливають на умови процесу свердління. Оптимізація геометрії різального інструмента здебільшого стосувалася визначення впливу подвійного головного кута [27], [34], ширини поперечної різальної кромки [35], спеціальної та ступінчастої геометрії свердла [5], [28], [31], конструкції допоміжної різальної кромки [30], [36], а також інструментального матеріалу [37], [38], покриття інструмента [39] на параметри якості отворів або характеристик процесу свердління.…”
Section: вплив різального інструментаunclassified
See 1 more Smart Citation
“…Геометрія різального інструмента, інструментальний матеріал та покриття є важливими факторами, які впливають на умови процесу свердління. Оптимізація геометрії різального інструмента здебільшого стосувалася визначення впливу подвійного головного кута [27], [34], ширини поперечної різальної кромки [35], спеціальної та ступінчастої геометрії свердла [5], [28], [31], конструкції допоміжної різальної кромки [30], [36], а також інструментального матеріалу [37], [38], покриття інструмента [39] на параметри якості отворів або характеристик процесу свердління.…”
Section: вплив різального інструментаunclassified
“…Для свердління пакетів найчастіше використовуються свердла з подвійним головним кутом 140°, 135° та 120°. Ці кути визначено як оптимальні для обробки отворів, як у шарі вуглепластику, так і у шарі титанового сплаву [31], [36]. Кут підйому гвинтової лінії змінюється від 15° до 30°.…”
Section: вплив різального інструментаunclassified
“…It has been reported that the reduction of the drill point angle is favorable for the reduction of the thrust force, which can lead to delamination control. Some authors have reported that smaller point angles strongly reduce the probability of burr formations and enhance the hole quality [ 33 ]. Nevertheless, this implies higher cutting tool lengths and operation times, also increasing instability [ 34 ].…”
Section: Introductionmentioning
confidence: 99%